2023
DOI: 10.1080/21645515.2023.2188857
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of primary and booster vaccination against COVID-19 by socioeconomic level: A nationwide cross-sectional registry study

Abstract: High and equitable COVID-19 vaccination coverage is important for pandemic control and prevention of health inequity. However, little is known about socioeconomic correlates of booster vaccination coverage. In this cross-sectional study of all Norwegian adults in the national vaccination program ( N = 4,190,655), we use individual-level registry data to examine coverage by levels of household income and education of primary (≥2 doses) and booster (≥3 doses) vaccination against COVID-19. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…After age, personal income, socioeconomic position, and origin ranked as the second-to-fourth-most important determinants of vaccine uptake. This is consistent with national registry-based studies from Norway, Sweden, and the United Kingdom, which found lower socioeconomic status and migration to be significantly associated with lower COVID-19 vaccine uptake [ 16 , 17 , 18 , 19 ]. Possible explanations for this are misinformation about the risks of disease due to COVID-19 and the effects of vaccination, as well as a lack of trust in authorities and the healthcare system.…”
Section: Discussionsupporting
confidence: 90%
“…After age, personal income, socioeconomic position, and origin ranked as the second-to-fourth-most important determinants of vaccine uptake. This is consistent with national registry-based studies from Norway, Sweden, and the United Kingdom, which found lower socioeconomic status and migration to be significantly associated with lower COVID-19 vaccine uptake [ 16 , 17 , 18 , 19 ]. Possible explanations for this are misinformation about the risks of disease due to COVID-19 and the effects of vaccination, as well as a lack of trust in authorities and the healthcare system.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study from Norway reported clear differences in vaccine uptake for two doses but also three or more booster doses regarding disposable household income and educational level. 17 Further, a study performed in the US state of Massachusetts showed that first dose and subsequent booster dose was greater in areas with higher income and education and was lower in areas with a greater percentage of Black, Latino and indigenous adults. 22 Additionally, among a specific population of healthcare workers in Wales, booster dose vaccine uptake was consistently lower among black healthcare workers, as well as those from deprived areas.…”
Section: Results In Relation To Previous Studiesmentioning
confidence: 99%
“…16 Booster vaccine uptake has been shown to be lower than initial vaccination with differences in individual socioeconomic factors including education and income. 17 A first step is to enrol individuals into a vaccination strategy by accepting the initial vaccination, but it is also of great importance to ensure they remain in the programme for the necessary booster doses. 18 The current understanding of the importance of individual sociodemographic factors vs contextual regional area surroundings in COVID-19 vaccine uptake is lacking, as is the potential driving factors that influence decisions to vaccinate or not on both the individual and contextual area level.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Large disparities have been observed in the uptake of COVID-19 vaccines both between countries, [8] , [9] but also within countries [9] . The within-countries disparities have among others been related to demographic, social, or economic differences [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . Various approaches, based on aggregated data, [13] , [17] on individual data from surveys, [15] , [20] or on individual data from health registers, [10] , [12] , [14] , [18] , [19] generally lead towards the same conclusions that lower socio-economic statuses and specific demographic situations (young age groups, people with a migration background) are associated with lower COVID-19 vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The within-countries disparities have among others been related to demographic, social, or economic differences [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . Various approaches, based on aggregated data, [13] , [17] on individual data from surveys, [15] , [20] or on individual data from health registers, [10] , [12] , [14] , [18] , [19] generally lead towards the same conclusions that lower socio-economic statuses and specific demographic situations (young age groups, people with a migration background) are associated with lower COVID-19 vaccine uptake. Despite these robust general patterns, there remains uncertainty about the importance and interplay of specific demographic and socio-economic factors.…”
Section: Introductionmentioning
confidence: 99%